MiR-92a and miR-486 are potential diagnostic biomarkers for mercury poisoning and jointly sustain NF-κB activity in mercury toxicity. Issue 1 (December 2017) - Ding, Enmin; Guo, Jun; Bai, Ying; Zhang, Hengdong; Liu, Xin; Cai, Wenyan; Zhong, Lixin; Zhu, Baoli
Abstract Occupational and environmental exposure to mercury is a public health concern worldwide. Although the altered epigenetic regulatory features, such as microRNA, have been associated with mercury exposure, the underlying molecular mechanism is not well illuminated. This study aimed to confirm that hsa-miR-92a and hsa-miR-486 are novel diagnostic biomarkers of occupational mercury poisoning, and to explore the underlying mechanism of miR-92a and miR-486 in mercury toxicity. RT-qPCR assays and receiver operating characteristics curve analyses were conducted to confirm the diagnostic value of miR-92a and miR-486 as biomarkers of occupational mercury poisoning. Dual-luciferase assay was applied to confirm the target gene of miR-92a and miR-486in vitro . Then, we established anin-vitro model where miR-92a and miR-486 were overexpressed or knocked down in HEK-293 and HUVEC cells. RT-qPCR and western blotting were used to analyze gene and protein expression levels. Cell apoptosis was determined by flow cytometry. Results show that miR-92a and miR-486 expression levels were up-regulated in workers exposed to occupational mercury. Upregulation of miR-92a and miR-486 may play a crucial role in mercury toxicity by jointly activating the NF-κB signaling pathway via targeting KLF4 and Cezanne, respectively.